2010
DOI: 10.1002/crat.200900609
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nucleation during hanging drop protein crystallization using HF Treatment of cover glasses

Abstract: We examined a simple approach, i.e., etching cover glasses using hydrofluoric acid (HF), to determine whether cover glass treatment enhances nucleation in hanging drop protein crystallization. Hen egg white lysozyme and proteinase K were used as the model proteins. We found that the treatment increased the success rate of crystallization. The results indicated that the simple treatment, which is easy to adopt without changing much in the hanging drop method, can be utilized as an alternative method to enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Compared with a smooth surface, the surfaces of the oxidized plates and the control plates both had much higher surface areas and many more small nanopores. Theoretically, the free-energy barrier for nucleation is decreased at a higher roughness (Guo et al, 2010;Liu et al, 2007). As shown in Table 3, the surface of the oxidized plates was smoother than that of the untreated plates.…”
Section: Larger Surface Area Could Promote the Evaporationmentioning
confidence: 85%
See 1 more Smart Citation
“…Compared with a smooth surface, the surfaces of the oxidized plates and the control plates both had much higher surface areas and many more small nanopores. Theoretically, the free-energy barrier for nucleation is decreased at a higher roughness (Guo et al, 2010;Liu et al, 2007). As shown in Table 3, the surface of the oxidized plates was smoother than that of the untreated plates.…”
Section: Larger Surface Area Could Promote the Evaporationmentioning
confidence: 85%
“…5, we could compare the contact areas between the OCP and control groups. The contact area was larger for the OCP than the control plates, and the larger contact area provided more opportunities for nucleation (Guo et al, 2010). Thus, there would be a greater likelihood of obtaining crystals in the OCP group.…”
Section: Discussionmentioning
confidence: 97%
“…Schmidt (8) argued that hanging drop or sitting drop vapor diffusion is a reasonably good screening method for identifying growth potential of a protein crystal. Since the protein crystallization process involves consecutive stages of nucleation and growth, successful crystallization first required nucleation (9). To this end, the hanging drop method serves as a robust technique for forming protein crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral substrate [11], silanised mica surface [12], lipid bilayers deposited on glass cover slips (for membrane protein crystallisation) [13,14], polymeric film containing poly- l -lysine or poly- l -aspartate ionisable groups [15], and a modified surface with a varying roughness [16,17] have all been proven to be useful for promoting protein crystallisation. These findings demonstrated that heterogeneous nucleation can effectively occur on large surfaces.…”
Section: Introductionmentioning
confidence: 99%